The Effect of Budgetary Slack, Organizational Commitment, Compensation, Human Capital and Governance on the Financial Performance of the Bureau Facilities and Logistic Construction of the POLRI - Retno Rahayuningsih; Nursanita Nasution; Rimi Gusliana Mais (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
This study aims to examine whether the effect of Budgetary Slack , Organizational Commitment , Compensation, Human Capital, and Governance on the financial performance of the Bureau of Logistics Facilities and Construction of the Police Headquarters (Case Study at the Bureau of Logistics Facilities and Construction at the Police Headquarters). Research is using the type of research causality approach is quantitative, which was measured by using a method based regression linear multiple with SPSS version 25.00. The population of the research this is the Institute of Logistics Police in the whole of Indonesia. The sample is determined based of Logistics Facilities and Construction of the Police Headquarters. The data used in this study are primary data. The data collection technique used a questionnaire which was distributed to 50 respondents. Testing the hypothesis by using test T and test F. The results of the study prove that (1) Budgetary Slack has an effect on the financial performance of the Police Headquarters Logistics Facilities and Construction Bureau, (2) Organizational Commitment has no effect on the financial performance of the Police Headquarters Logistics Facilities and Construction Bureau, (3) Compensation has no effect on the Facility Bureau financial performance. And Construction Logistics Headquarters of Police, (4) Human Capital affect on the performance of financial Bureau of facilities and Construction Logistics Headquarters of Police , (5) Governanceno effect on the performance of financial Bureau of facilities and Construction Logistics Headquarters Police.